Utilization of resources: An ethical issue: The anti-commons and the aquaculture case - Filipe, J.; Ferreira, M. A. M.; Coelho, M. (Ethical issues and social dilemmas in knowledge management: Organizational innovation, 2011)
Anti-Commons Theory is an interesting theme that is being developed in the area of property rights since the 80’s. It intends to explain why an “anti-commons” emerges and why resources may be prone to under-use. In an anti-commons situation there are too many exclusion rights that lead to the under-use of resources. In Portugal, too many people (and institutions) have been involved in the approval processes of aquaculture projects. They may be involved in reaching a decision about the approval of a project which gives rise to the under-utilization of the resources that promoters aimed to exploit. Actually, it takes so long to approve a project that the time required for its implementation may be excessively delayed. This kind of problem results typically from bureaucratic environment. An ethical problem rises with this phenomenon. Projects may not go forward and all the amounts spent in the project will be lost. Besides, a viable project simply can be gone, with all the inherent losses of value.